(3faM GdWjH ef ZUf GdCfOdS GdQWjH hPcQ hRjQgG dSGf GdOjf GHf GdNWjHs - (3GdebQj , CMeO Hf eMeO Hf CMeO Hf jMji GdJdeSGfj, CHh GdYHGS,J (B1041 (3g` s
(3ChdgG (B:s
(3jHOC GdHGH GdSGOS ai eUfaGJg dSGf GdOjf GdNWjH s
(3BNQgG (B:s
(3BNQ bUjOI GHf RjOhf GdfhfjI s
(3LRA BNQ ef fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B78s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B296 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B323 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeY GdCMeOi HWfWG (B((3SjQ hJQGLe (B128) s
Keywords: (3GdJGQjNs